A Synopsis of the Nigerian Democracy - Akindoyin, Dare Isaac; Badru, Ronald Olufemi (Kashere Journal of Politics and International Relations, 2024)
This research paper makes a critical analysis of Nigerian Democracy. In the Global North and Global South, democracy has emerged as the most viable governmental system. Since its transition from military rule to democracy in 1999, Nigeria has navigated a complex political landscape marked by progress as well as persistent challenges. That is, the Nigerian State has navigated a tumultuous journey through various forms of democracy, driven by the conviction that it represents the sole acceptable political framework for the nation. Despite encountering considerable challenges, including the perceived inadequacies of the elections in 2003, 2007, and the mixed outcomes of those in 2011 and 2015, 2019 and 2023, the commitment to democracy remains deeply ingrained among the populace. With the adoption of content analysis and the liberal theory of state as a theoretical framework, the research critically explores the Nigerian Democracy since the fourth republic. The findings of this research paper are that, the fundamental measure of democracy lies in effective or good governance while good governance entails; improved living standards for the average person, heightened public perception of fair and judicious allocation and use of resources, restoration and functionality of essential infrastructure, economic diversification and increased trust in the electoral process. The research paper recommends citizens attitudinal change, electoral reforms, political party regulation, civic education, civil society engagement, judicial independence, anti-corruption measures, decentralization of power, ethnic and religious harmony, for effective consolidation of the Nigerian democracy.